Compound Odontoma in Anterior Maxilla in a 10-year-old Pediatric Patient: A Case Report with 44 Denticles Extracted - Priyanka Aggarwal; Kopal Singh; Pallavi Anand; Pulkit Jhingan; Manvi Malik; Shivani Mathur (Journal of South Asian Association of Pediatric Dentistry)
Background: Odontomas are the most common odontogenic hamartomas worldwide. These can be compound or complex. Case description: A 10-year-old male child reported a chief complaint of delayed eruption of permanent teeth in the upper front tooth region. Clinical examination revealed unerupted 21 and 22 with retained deciduous lateral incisors. Further, an orthopantomogram (OPG) was done, which revealed the presence of multiple small radiopaque teeth-like structures in the apical region of the retained deciduous lateral incisor 62 surrounded by a narrow radiolucent halo. Cone-beam computed tomography (CBCT) was done as a confirmatory test. A final diagnosis of compound odontoma was made, and conservative surgical enucleation was the treatment of choice. A total of 44 denticles were removed along with the follicle. They were sent for a biopsy, which confirmed the diagnosis as compound odontoma. Conclusion: It is crucial to diagnose these tumors early for a better prognosis.